A Neo Tropical Companion - Stewart, Jamie (punctum books, 2012)
A Neo Tropical Companion is the first collection of haikus written by Xiu Xiu singer, Jamie Stewart. This is the first time his haikus, which have been featured in several literary journals and small press releases, will be comprehensively collected. Two thirds of the work will include new poems written for specifically for this book. The title, A Neo Tropical Companion, comes from an antiquated guide book to North East South America that Stewart found molding on the ground in the jungle. The poems, written in the classical Japanese poetry form, concern death, uncertainty, cats, being on weird tours, horrible sex, hating other people, bird watching in Guyana, and growing up in a dim and boxed-in valley.